مشكلات رغبة الطلاب في تعلم اللغة العربية بالمرحلة الابتدائية: دراسة حالة سياقية لتفاعل العوامل النفس‌لغوية والبيداغوجية - Siti Maimuna; Yayah Robiatul Adawiyah (Darul Yasin Al Sys, 2026)
The problem lies in the low interest of fifth-grade students at Al-Zainiyyah Elementary School in learning Arabic. The research gap appears in the limited attention of previous studies to addressing this problem from a local contextual perspective that integrates psychological and pedagogical factors within a specific institution. The methodology adopted a qualitative approach as a case study, in which data were collected through participant observation, semi-structured interviews with the teacher, principal, and students, and documents, and were analyzed according to the interactive model of Miles, Huberman, and Saldaña. The findings reveal that weak learning interest results from a negative intersection between internal psycholinguistic obstacles, such as language anxiety and difficulty memorizing vocabulary, and a monotonous external teaching style based on lecturing; nevertheless, the findings showed surprising behavioral variation and an immediate shift toward active participation when language games were introduced. The conclusion indicates that learning interest is not a static variable, but rather a dynamic response governed by the quality of external instructional stimuli capable of dismantling students’ mental barriers. The implications are reflected in the need to reconstruct a differentiated curriculum matrix and institutionalize game-based learning and gamification strategies as a sustainable environment that meets the cognitive needs of elementary school children.